2019
DOI: 10.3390/cells8111461
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs upon Epithelial-to-Mesenchymal Transition in Inflammatory Bowel Disease

Abstract: Increasing evidence suggest the significance of inflammation in the progression of cancer, for example the development of colorectal cancer in Inflammatory Bowel Disease (IBD) patients. Long-lasting inflammation in the gastrointestinal tract causes serious systemic complications and breaks the homeostasis of the intestine, where the altered expression of regulatory genes and miRNAs trigger malignant transformations. Several steps lead from acute inflammation to malignancies: epithelial-to-mesenchymal transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 166 publications
0
21
0
1
Order By: Relevance
“…This process is associated with the formation of intestinal fibrosis and may play a role in the development of IBD-related colorectal cancer [20]. We have previously reported that the expression of EMT activating genes significantly increased both in the inflamed colon samples of TNBS treated rats as well as in IBD patients [13,15,19]. In addition, the expression of growth factors (EGR1, FGF2 and FGF7), signal transducer molecules (JAK2, NOTCH2 and HIF1α), EMT inducing transcriptional factors (ZEB2, SNAI1), extracellular matrix remodeler MMP9 and mesenchymal markers (LOX and VIM) are all upregulated in the inflamed colon tissues, while the expression of the epithelial marker CDH1 decreased [13,15,19].…”
Section: Correlation Between Murine and Human Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is associated with the formation of intestinal fibrosis and may play a role in the development of IBD-related colorectal cancer [20]. We have previously reported that the expression of EMT activating genes significantly increased both in the inflamed colon samples of TNBS treated rats as well as in IBD patients [13,15,19]. In addition, the expression of growth factors (EGR1, FGF2 and FGF7), signal transducer molecules (JAK2, NOTCH2 and HIF1α), EMT inducing transcriptional factors (ZEB2, SNAI1), extracellular matrix remodeler MMP9 and mesenchymal markers (LOX and VIM) are all upregulated in the inflamed colon tissues, while the expression of the epithelial marker CDH1 decreased [13,15,19].…”
Section: Correlation Between Murine and Human Samplesmentioning
confidence: 99%
“…To validate our transcriptome data, first we compared the RNA-Seq results to our previous data on gene expression changes related to epithelial-to-mesenchymal transition (EMT) [13,15,19]. Upon EMT, epithelial cells lose their epithelial characteristics, their cell-cell connections disintegrate and cell motility enhances.…”
Section: Correlation Between Murine and Human Samplesmentioning
confidence: 99%
“…miRNAs have a huge potential as biological markers, because there are key molecular players in regulating a multitude of cellular processes, including IBD development [23,24]. Specific miRNA signatures have been observed in IBD, associated with canonical signaling pathways regulating autophagy, inflammation, fibrosis, or EMT [25]. One of the analyzed miRNAs in the present paper is miR-155 which was shown to inhibit the suppressor of cytokine signaling (SOCS1)-a negative regulator of the Janus kinase/signal transducers and activators of transcription (JAK/STAT signaling); thus, elevating the expression of miR-155 could enhance inflammation in the intestine of IBD patients by immune system perturbation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Specific miRNA signatures have been observed in IBD, associated with canonical signaling pathways regulating autophagy, inflammation, fibrosis, or EMT [25]. One of the analyzed miRNAs in the present paper is miR-155 which was shown to inhibit the suppressor of cytokine signaling (SOCS1)-a negative regulator of the Janus kinase/signal transducers and activators of transcription (JAK/STAT signaling); thus, elevating the expression of miR-155 could enhance inflammation in the intestine of IBD patients by immune system perturbation [25,26]. In our study, we noticed an increased expression of miR-155-5p in both inflamed tissue and, most important, also adjacent tissue of patients with CD, suggesting that elevated miR-155-5p expression contributes to CD development.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, EMT can be observed during embryogenesis, tissue development and wound healing [48]. It is also a common phenomenon during carcinogenesis and can either induce or coexist with various malignancies such as breast cancer, thyroid cancer, cholangiocarcinoma, non-small cell lung carcinoma, colorectal cancer, inflammatory bowel disease or GC [49][50][51][52][53][54][55][56][57][58][59][60]. During the EMT process, ECs undergo a series of biochemical reactions that eventually lead to alterations in the cells' morphology, especially the loss of the polarity of cells [17,61].…”
Section: Figurementioning
confidence: 99%